Development of fuzzy logic controller design techniques - Wu, Jian. (2008)
This thesis presents the development of fuzzy logic controller design which includes two parts: the fuzzy tuning PID method and the hybrid fuzzy-neural method corresponding to Mamdani type and Takagi and Sugeno type. This thesis describes a fuzzy tuning scheme of PID controllers for process control.